Nano parçacık içeren betonlarda kırılma mekaniği analizleri - Negin, Mesud; Çağlar, Nilgün Merve; Topgül, Sebahattin; Belgin, Çağatay Mehmet; Çağlar, Yasin; Şener, Sıddık; Boduroğlu, Veysel Baran (My University, 2014)
[Abstract Not Available]
15.04.2014 00:00